Mission-Oriented Policy for a Greener Nickel Industry in Indonesia: Challenges and Pathways - Wijayanto, Ari; Hafizhah, Annisa; Aqbar, Muhammad Rudy (Talenta Publisher, Universitas Sumatera Utara, 2024)
This article explores policy strategies necessary to promote a sustainable and eco-friendly nickel mining industry in Indonesia, especially as it relates to the electric vehicle (EV) sector. With Indonesia's substantial nickel reserves, demand is expected to rise sharply, driven by the global shift to EVs. However, nickel production is a significant contributor to greenhouse gas emissions, with one kilogram of nickel generating approximately 13 kilograms of CO₂. By 2035, Indonesia's demand for nickel for EV batteries alone could lead to 773 thousand tons of CO₂ emissions. This paper aims to assess green-oriented policies that could mitigate these impacts, drawing on Mariana Mazzucato’s Mission-Oriented Policies as a strategic framework. The methodology used includes literature review and case study analysis of successful policies in other countries, such as renewable energy integration in mining and efficient recycling methods. Three primary strategies are examined: improving energy efficiency, incorporating renewable energy, and sustainable recycling. Findings indicate that these policies could foster sustainable growth, reduce emissions, and align with Indonesia's green economy goals. This paper concludes that implementing a mission-oriented, environmentally sustainable approach could pave the way for a greener, more resilient nickel industry.